Design & Development of a Computer Controlled Tensile Strength Testing Machine for Testing of Strings & Fabrics - Sharma, Ravi Babu; Rai, Jitendra Kumar (International Journal of Advanced Engineering Research and Science, 2021)
Tensile testing is a primary material science test in which a sample is tension-proof until it is failure. Test results are frequently used to select an application material, to verify quality and to forecast how the material reacts with other forces. The features assessed directly by a tensile test include maximum tensile strength, maximum length and a reduction of the area. From these measures the following characteristics can also be determined: Young modulus, the ratio of Poisson, yield strength and stress resistance. Testing machine is used for the development and maintenance of better information on known materials or the development of new materials. There are many test machines, but the most common of these is the one that tests tensions, compression and bending of the materials. For the test specimen to be tested, the engine must have the proper characteristics. Three major parameters exist: strength, speed, accuracy and precision. The test machine is mainly used in the creation of the stress line diagram. The computer algorithm may be applied to compute the yield strength, tensile force, youth module or total elongation once the diagram has been generated. The author has designed & fabricated a model for demonstration of the techniques employed using viper motor (DC motor) for force exertion, load cell & instrumentation amplifier of reading force, ultrasonic distance sensor for measurement of displacement. Simultaneously a tripod mounted webcam is employed to capture real time video & image processing & employed to compute displacement on the basis of motor movement.